The effects of extended public transport operating hours and venue lockout policies on drinking-related harms in Melbourne, Australia: Results from SimDrink, an agent-based simulation model. - Scott, N.; Hart, Aaron; Wilson, James; Livingston, M.; Moore, David; Dietze, P. (Elsevier BV, 2016)
Background: The late-night accessibility of entertainment precincts is a contributing factor to acute drinking-related harms. Using computer simulation we test the effects of improved public transport (PT) and venue lockouts on verbal aggression, consumption-related harms and transport-related harms among a population of young adults engaging in heavy drinking in Melbourne. Methods: Using an agent-based model we implemented: a two-hour PT extension/24-hour PT; 1 am/3 am venue lockouts; and combinations of both. Outcomes determined for outer-urban (OU) and inner-city (IC) residents were: the number of incidents of verbal aggression inside public and private venues; the number of people ejected from public venues for being intoxicated; and the percentage of people experiencing verbal aggression, consumption-related harms and transport-related harms. Results: All-night PT reduced verbal aggression in the model by 21% but displaced some incidents among OU residents from private to public settings. Comparatively, 1 am lockouts reduced verbal aggression in the model by 19% but led to IC residents spending more time in private rather than public venues where their consumption-related harms increased. Extending PT by 2 h had similar outcomes to 24-hour PT except with fewer incidents of verbal aggression displaced. Although 3 am lockouts were inferior to 1 am lockouts, when modelled in combination with any extension of PT both policies were similar. Conclusions: A two-hour extension of PT is likely to be more effective in reducing verbal aggression and consumption-related harms than venue lockouts. Modelling a further extension of PT to 24 h had minimal additional benefits but the potential to displace incidents of verbal aggression among OU residents from private to public venues.